Regulating Early Childhood Mathematical Provision: An Exploration Across the Sectors (LEARNing Landscapes, 2013)
Effective mathematics provision is a central goal within Early Childhood Education. However, the choices that teachers make within Centers and new entrant classrooms are influenced by deeper understandings about the kinds of arrangements that allow young students to enhance their learning. This paper explores similarities and differences with respect to the practices and processes in Early Childhood Centers and in new entrant classrooms. Drawing on Foucauldian concepts, the analysis reports that practices and processes were at odds across the two sectors. The challenge is to offer young learners a more seamless mathematical experience.
Keywords: early childhood; education; mathematics; Foucauldian concepts